Potency of Trichoderma sp., antagonistic fungi derived from soil rhizospere, against two pathogens: Botryodiplodia theobromae Pat. and Fusarium sp. wilt in Vitro - Unun - Triasih (Gontor AGROTECH Science Journal, 2020)
This study aims to to detennine the effectiveness  of Trichoderma sp. as biocontrol  agent  through suitability  test and test  of its inhibition  against  pathogens  Botryodiplodia theobromae Pat. and  Fusarium sp. through  antagonistic  testing. Four Trichoderma sp. isolates:  Trichoderma harzianum and Trichoderma viride from citrus plants, Trichoderma sp. from Manalagi  apple plants, Trichoderma sp. from strawberry  plants were tested  against  Fusarium sp. isolates  and Botryodiplodia theobromae Pat. isolates.  There  are  two treatments: suitability test of four Trichoderma sp. isolates and their inhibitory tests on Botryodiplodia theobromae Pat and Fusarium sp. Observations  included  presence  or absence  of inhibition  zones,  growth  of pathogenic  control pathways   and  pathogenic   pathways   in  dual  culture  with  antagonists.   Test  results  showed  that  the  four Trichoderma  sp. isolatees did not show any inhibitory  zones, which indicated that the tested antagonistic  fungi were  mutually  compatible   and  could  be  combined.  The  best  percentage   of  inhibition  against  pathogens Fusarium sp and Botryodiplodia theobromae Pat came from Trichoderma  sp from strawberry plants by 84.62% and82.75%.